Genetic outcomes in children with developmental language disorder: a systematic review - van Wijngaarden, Vivian; de Wilde, Hester; Mink van der Molen, Dieuwke; Petter, Jildo; Stegeman, Inge; Gerrits, Ellen; Smit, Adriana L.; van den Boogaard, Marie-José (Frontiers in Pediatrics, 2024)
Introduction Developmental language disorder (DLD) is a common childhood condition negatively influencing communication and psychosocial development. An increasing number of pathogenic variants or chromosomal anomalies possibly related to DLD have been identified. To provide a base for accurate clinical genetic diagnostic work-up for DLD patients, understanding the specific genetic background is crucial. This study aims to give a systematic literature overview of pathogenic variants or chromosomal anomalies causative for DLD in children. Methods We conducted a systematic search in PubMed and Embase on available literature related to the genetic background of diagnosed DLD in children. Included papers were critically appraised before data extraction. An additional search in OMIM was performed to see if the described DLD genes are associated with a broader clinical spectrum. Results The search resulted in 15,842 papers. After assessing eligibility, 47 studies remained, of which 25 studies related to sex chromosome aneuploidies and 15 papers concerned other chromosomal anomalies (SCAs) and/or Copy Number Variants (CNVs), including del15q13.1–13.3 and del16p11.2. The remaining 7 studies displayed a variety of gene variants. 45 (candidate) genes related to language development, including FOXP2, GRIN2A, ERC1, and ATP2C2. After an additional search in the OMIM database, 22 of these genes were associated with a genetic disorder with a broader clinical spectrum, including intellectual disability, epilepsy, and/or autism. Conclusion Our study illustrates that DLD can be related to SCAs and specific CNV's. The reported (candidate) genes (n = 45) in the latter category reflect the genetic heterogeneity and support DLD without any comorbidities and syndromic language disorder have an overlapping genetic etiology.